The Suitability of KOMSAS Novels for Inculcating Open-Mindedness Among Secondary School Students: (Keupayaan Novel Komsas Menerapkan Nilai Perpaduan Bersikap Terbuka dalam Kalangan Murid) (Malay Literature, 2020)
Ethnic harmony has existed for a long time in this country. The multi-ethnic nature of our society remains unchanged even if there are occasional disputes in the economic sector and political or social spheres. To ensure the continuance of ethnic harmony, the Standard National Secondary School Curriculum (Kurikulum Standard Sekolah Menengah or KSSM) was introduced by the Ministry of Education. In this curriculum, the principles of national unity are to be inculcated through literary works taught in the literature component (KOMSAS) in schools. One of these principles is open-mindedness. This study aims to employ Lukac's Reflection Theory to examine the extent to which KOMSAS novels can be used to inculcate unity among students by analysing, discussing and clarifying the principle of open-mindedness, as specified in the KSSM. This is a qualitative study analysing the contents of the novel Jendela Mengadap Jalan usiing the Reflective Theory of Lukacs adapted according to the open-mindedness principle in the KSSM. The findings of this research show that the novel Jendela Mengadap Jalan is infused with the principle of open-mindedness as outlined in the KSSM. To examine the principles of unity in the novel, the researcher approached two aspects, namely dialogue and portrayal. It is found that the principles of unity conveyed in this novel should be applied and practiced by students in their daily lives. Teachers should convey open-mindedness to their students wisely using persuasion and warning. The implications of this research are that KOMSAS novels can be used to foster unity and ethnic harmony in this country.Keywords: Education; unity values; Literature Component (KOMSAS) novels; KSSM; Lukacs's Reflection Theory